A new model for the legal pluralist study of children's rights, illustrated by a case study on the child's right to education in the Central African Republic. Issue 1 (2nd January 2019) - Hopman, Marieke Janne
Abstract: When trying to understand why children's rights are being violated, legal pluralism has been used as a theoretical framework for the empirical study of children's rights by relatively few researchers. In most of these cases, it is unclear why a certain social phenomenon is categorized as "law, " and research on smaller legal orders related to children, such as the school and the household, is lacking. My hypothesis is that for children, law is mostly what their parents or their teachers tell them. Therefore, this law, that we find when looking at law through children's eyes, has to be recognized as part of a complete picture of law influencing the protection and/or violation of children's rights. In the current article, I present an alternative legal pluralist theoretical and methodological framework for the research of children's rights. To go beyond mere theory, I will show how I applied the theory to a case study on the child's right to education in the Central African Republic (CAR) and present its results.